Effect of E-Performance, Work Engagement and Organizational Culture on Employee Performance tith Job Satisfaction as Intervening - Tiara Ismawati; Elisabet siahaan; Beby Karina F Sembiring (Journal Research of Social Science, Economics, and Management, 2022)
The application of e-performance-based performance appraisal will help organizations evaluate the performance of their employees effectively and efficiently. High work engagement between employees and their work will make employees maximize their work, so that they will be able to improve organizational performance. An organizational culture that is adhered to by employees will make it easier for the organization to apply the rules and carry out its work program. The purpose of this study was to analyze the effect of e-performance-based performance appraisal, work engagement, and organizational culture on employee performance with job satisfaction as an intervening variable on employees of Doloksanggul Hospital, Humbang Hasundutan Regency. The population in this study were 224 hospital employees with a sample of 143 respondents using purposive sampling technique. Data were analyzed using descriptive statistical analysis and path analysis through IBM SPSS Statistics. The results showed that e-performance based performance appraisal, work engagement, and organizational culture directly had a positive and significant effect on performance. Furthermore, e-performance-based performance appraisal, work engagement, and organizational culture directly have a positive and significant effect on job satisfaction. Job satisfaction mediates the relationship between performance appraisal based on e-performance, job involvement and organizational culture on performance.